Simulation of reactive flow over a parabolic vertical plate using MATLAB - Pushparaj, Sivakumar; Ramalingam, Balaji; Adhimoolam, Ramesh; Mohan Reddy, P. Venkata; Srinivasan, Andal; Rajamanickam, Muthucumaraswamy (Indonesian Journal of Electrical Engineering and Computer Science, 2025)
This article examines how fluid flows around an infinitely large, parabolic-shaped vertical plate, which is heated at an exponentially accelerating rate and undergoes a chemical reaction with the fluid. The plate’s temperature increases at an exponential rate, adding complexity to the heat transfer process. Additionally, the fluid undergoes a chemical reaction in this environment, impacting both the flow and concentration of chemical species. The article includes graphs that show how different parameters such as the rate of temperature increase, strength of thermal radiation, and reaction rate, effect the flow, heat, and concentration profiles. This graphical analysis provides a visual understanding of how each parameter influences the behavior of the fluid.